Mn12‐Acetate Complexes Studied as Single Molecules. Issue 2 (8th December 2021) - Tombers, Matthias; Meyer, Jennifer; Meyer, Jonathan; Lawicki, Arkadiusz; Zamudio‐Bayer, Vicente; Hirsch, Konstantin; Lau, J. Tobias; von Issendorff, Bernd; Terasaki, Akira; Schlathölter, Thomas A.; Hoekstra, Ronnie A.; Schmidt, Sebastian; et al.
Abstract: The phenomenon of single molecule magnet (SMM) behavior of mixed valent Mn12 coordination clusters of general formula [Mn III 8 Mn IV 4 O12 (RCOO)16 (H2 O)4 ] had been exemplified by bulk samples of the archetypal [Mn III 8 Mn IV 4 O12 (CH3 COO)16 (H2 O)4 ] (4) molecule, and the molecular origin of the observed magnetic behavior has found support from extensive studies on the Mn12 system within crystalline material or on molecules attached to a variety of surfaces. Here we report the magnetic signature of the isolated cationic species [Mn12 O12 (CH3 COO)15 (CH3 CN)] + (1) by gas phase X‐ray Magnetic Circular Dichroism (XMCD) spectroscopy, and we find it closely resembling that of the corresponding bulk samples. Furthermore, we report broken symmetry DFT calculations of spin densities and single ion tensors of the isolated, optimized complexes [Mn12 O12 (CH3 COO)15 (CH3 CN)] + (1), [Mn12 O12 (CH3 COO)16 ] (2), [Mn12 O12 (CH3 COO)16 (H2 O)4 ] (3), and the complex in bulk geometry [Mn III 8 Mn IV 4 O12 (CH3 COO)16 (H2 O)4 ] (5) . The found magnetic fingerprints – experiment and theory alike – are of a remarkable robustness: The Mn IV 4 core bears almost no magnetic anisotropy while the surrounding Mn III 8 ring is highly anisotropic. These signatures are truly intrinsic properties of the Mn12 core scaffold within all of these complexes and largely void of the environment. This likely holds irrespective of bulk packing effects. Abstract : Mn12 O12 (RCOO)16 complexes have been the guinea pigs of research on single molecular magnets in the bulk and on surfaces before. Here, novel XMCD studies of isolated ionic samples with same Mn12 scaffolds yield magnetic fingerprints much like bulk samples. Advanced computations of single ion tensors find high anisotropies only on the outer Mn III 8 ring. Intrinsic magnetic properties of the Mn12 scaffold seem robust against the environment.